2016
DOI: 10.1016/j.ssmph.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

How can GPS technology help us better understand exposure to the food environment? A systematic review

Abstract: PurposeGlobal Positioning Systems (GPS) are increasingly being used to objectively assess movement patterns of people related to health behaviours. However research detailing their application to the food environment is scarce. This systematic review examines the application of GPS in studies of exposure to food environments and their potential influences on health.MethodsBased on an initial scoping exercise, published articles to be included in the systematic review were identified from four electronic databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 59 publications
1
59
0
Order By: Relevance
“…For example one study suggested that modelling underestimated walking route length by 21%, but over-estimated food outlet exposure by 25% 78 . A systematic review of GPS technology (six studiesfive from US and one in the UK) found that while use of technology was in its infancy, being able to record and analyse patterns of mobility, is of huge value 79 . However, two issues are apparent.…”
Section: Discussionmentioning
confidence: 99%
“…For example one study suggested that modelling underestimated walking route length by 21%, but over-estimated food outlet exposure by 25% 78 . A systematic review of GPS technology (six studiesfive from US and one in the UK) found that while use of technology was in its infancy, being able to record and analyse patterns of mobility, is of huge value 79 . However, two issues are apparent.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, based on our findings in this study, workplace proximity to fast‐food establishments might matter more for the BMI of males. More research needs to be done to confirm these conclusions, including using better measures of food establishment exposure, perhaps through use of mobile devices …”
Section: Discussionmentioning
confidence: 99%
“…More research needs to be done to confirm these conclusions, including using better measures of food establishment exposure, perhaps through use of mobile devices. 36 It may appear surprising that the correlation between the neighborhood random effects on residents and workers of the same neighborhood should be 0 (or negative). We conjecture that this reflects a reliance on distinct fast-food outlets or the same outlets at different times by residents and employees of the same neighborhood.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been completed in the last years on the food environment using GPS, and they have both a sufficient time window and over a hundred individuals. A sample of such studies is provided in Table 1, and a dedicated 2016 review details the use of GPS dataset for the food environment [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Indeed, using such rich datasets allow us to develop, calibrate, and validate models that go beyond the proximity hypothesis. However, the acquisition, cleaning, and analysis of detailed spatial datasets of food behaviours have typically been done in a separate strand of literature (primarily geography [22]) from the ones on developing ABMs of food behaviours (typically public health nutrition and obesity research [23]). Finally, policies can tackle several determinants of food behaviours at the same time, in ways that depend on a local constituency's characteristics and agenda.…”
Section: Introductionmentioning
confidence: 99%